Magnetic Resonance Imaging and Spectroscopy Evidence of Efficacy for Adrenal and Gonadal Hormone Replacement Therapy in Anorexia Nervosa - Vajapeyam, Sridhar (Bone, 2018)
PURPOSE: Dehydroepiandrosterone (DHEA) + estrogen/progestin therapy for adolescent girls with anorexia nervosa (AN) has the potential to arrest bone loss. The primary aim of this study was to test the effects of DHEA+ estrogen/progestin therapy in adolescent girls with AN on bone marrow in the distal femur using magnetic resonance imaging (MRI) and spectroscopy. METHODS: Seventy adolescent girls with AN were enrolled in a double blind, randomized, placebo-controlled trial at two urban hospital-based programs. INTERVENTION: Seventy-six girls were randomly assigned to receive 12 months of either oral micronized DHEA or placebo. DHEA was administered with conjugated equine estrogens (0.3mg daily) for 3 months, then an oral contraceptive (20μg ethinyl estradiol/0.1mg levonorgestrel) for 9 months. The primary outcome measure was bone marrow fat by MRI and magnetic resonance spectroscopy (MRS). RESULTS: T2 of the water resonance dropped significantly less in the active vs. placebo group over 12 months at both the medial and lateral distal femur (p=0.02). Body mass index (BMI) was a significant effect modifier for T1 and for T2 of unsaturated (T2(unsat)) and saturated fat (T2(sat)) in the lateral distal femur. Positive effects of the treatment of DHEA + estrogen/progestin were seen primarily for girls above a BMI of about 18 kg/m(2). CONCLUSIONS: These findings suggest treatment with oral DHEA+ estrogen/progestin arrests the age- and disease-related changes in marrow fat composition in the lateral distal femur reported previously in this population.